1993
DOI: 10.1161/01.hyp.22.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Chlorothiazide. How the thiazides evolved as antihypertensive therapy.

Abstract: -have left little time to look back for looking forward, unless invited to do so. This is about chlorothiazide, how the thiazides evolved, and how they were expected to relate to edema and hypertension. Saluretics: Concepts and MethodologyMy Wisconsin training helped create a capability to identify clinical correlates of a "disease" with a best relevant expression of that function for manipulation in a most appropriate laboratory animal. Discovery of the thiazides was a second example of this from our research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…These drugs, mainly used as diuretics, contain the benzothiadiazine group in their structure. This diuretic class with the first-in-class drug chlorothiazide was introduced in 1957 upon chemical modification of CA inhibitors [ 32 , 33 ]. Currently, thiazide diuretics are often used as first-line treatment for hypertension, despite that their exact mechanism of action is still unclear–it depends on the time course of the drug use: the acute action relies on the inhibition of Na + /Cl - cotransporter, while the mechanism of chronic action still has to be clarified [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These drugs, mainly used as diuretics, contain the benzothiadiazine group in their structure. This diuretic class with the first-in-class drug chlorothiazide was introduced in 1957 upon chemical modification of CA inhibitors [ 32 , 33 ]. Currently, thiazide diuretics are often used as first-line treatment for hypertension, despite that their exact mechanism of action is still unclear–it depends on the time course of the drug use: the acute action relies on the inhibition of Na + /Cl - cotransporter, while the mechanism of chronic action still has to be clarified [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trichlormethiazide (TCMZ), systematic name 6-chloro-3-(dichloromethyl)-1,1-dioxo-3,4-dihydro-2H-1 6 ,2,4-benzothiadiazine-7-sulfonamide (C 8 H 8 Cl 3 N 3 O 4 S 2 ), is a diuretic drug derived from thiazide, the precursor of a classic family of diuretic compounds, discovered in the 1950s. The first approved drug of this class, chlorothiazide, was marketed under the trade name Diuril in 1958 (Beyer, 1993). The compound under study, trichlormethiazide, has a similar chemical structure to hydrochlorothiazide, the most prescribed member of the group (Hripcsak et al, 2020).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Hydrochlorothiazide (1, 6-chloro-3,4-dihydro-2H-benzo[e]- [1,2,4]thiadiazine-7-sulfonamide 1,1-dioxide, HCT, Scheme 1) was developed and put on the market in the late 1950s as one of the first efficient antihypertensive drugs. 1−6 Despite the fact that it has been on the market for more than 60 years, it still constitutes a backbone of antihypertensive therapy as a key component of many fixed dose combination products with angiotensin receptor blockers, ACE inhibitors, and other antihypertensive agents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, literature reports already highlight the preparation of Nnitroso-hydrochlorothiazide (2, 6-chloro-4-nitroso-3,4-dihydro-2H-benzo[e] [1,2,4]thiadiazine-7-sulfonamide 1,1-dioxide, NO-HCT, Scheme 1); 37,38 however, its reactivity was not explored in a broader context. In this report, we demonstrate that NO-HCT 2 is unstable in aqueous conditions at pH 1 to 8 and readily decomposes to several degradation products among which formaldehyde, aminobenzenesulfonic acid (3, 2-amino-4chloro-5-sulfamoylbenzenesulfonic acid, ABSA, Scheme 1), thiatriazine (4, 6-chloro-2H-benzo[e] [1,2,3,4]thiatriazine-7sulfonamide 1,1-dioxide, Scheme 1), and HCT 1 are the predominant ones. Moreover, independent synthesis of the HCT-diazonium salt (5, 5-chloro-2,4-disulfamoylbenzenediazonium, Scheme 1) and study of its stability and reactivity have demonstrated that it is relatively stable only in highly acidic and anhydrous conditions in aprotic solvents (e.g., acetonitrile), whereas it decomposes rapidly in neutral or acidic aqueous medium to ABSA 3 instead of the typical diazonium salt hydrolysis and reduction products, which were not detected in the NO-HCT 2 degradation pathway.…”
Section: ■ Introductionmentioning
confidence: 99%